Botanical Drug Extracts Combined With Biomaterial Carriers for Osteoarthritis Cartilage Degeneration Treatment: A Review of 10 Years of Research - Panyun Mu; Jie Feng; Yimei Hu; Feng Xiong; Xu Ma; Linling Tian (Frontiers Media S.A., 2022)
Osteoarthritis (OA) is a long-term chronic arthrosis disease which is usually characterized by pain, swelling, joint stiffness, reduced range of motion, and other clinical manifestations and even results in disability in severe cases. The main pathological manifestation of OA is the degeneration of cartilage. However, due to the special physiological structure of the cartilage, once damaged, it is unable to repair itself, which is one of the challenges of treating OA clinically. Abundant studies have reported the application of cartilage tissue engineering in OA cartilage repair. Among them, cell combined with biological carrier implantation has unique advantages. However, cell senescence, death and dedifferentiation are some problems when cultured in vitro. Botanical drug remedies for OA have a long history in many countries in Asia. In fact, botanical drug extracts (BDEs) have great potential in anti-inflammatory, antioxidant, antiaging, and other properties, and many studies have confirmed their effects. BDEs combined with cartilage tissue engineering has attracted increasing attention in recent years. In this review, we will explain in detail how cartilage tissue engineering materials and BDEs play a role in cartilage repair, as well as the current research status.